RARE CLINICAL CASE: FORMATION OF ARTIFICIAL URETHER AFTER AMPUTATION OF THE PENIS - V. A. Vorobyev (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
A brief overview of the problem of the penis amputation, the consequences and possible methods for their resolution is presented. The article describes epidemiological situation and the main causes of the penis amputation. The modern existing ways of surgical treatment are illuminated, depending on the cause of amputation. Variants of phalloplasty are described. A rare clinical case of a patient undergoing amputation of the penis and adjuvant chemoradiotherapy for penile cancer in the third stage is presented. Subsequently, the patient underwent obliteration of the urethraperineostomy, as a result of which a cystostomy was performed. The patient complained of the impossibility of independent urination, a decrease in the quality of life. The presence of the crotch stoma did not suit the patient, he asked to restore the ability to upstanding urination. To eliminate these problems, fulfill the requirements, we reconstructed the patient's preserved and the formed the artificial part of the urethra. In the postoperative period, a complication occurred - urethral fistulas, which required a repeated corrective operation. Described are remote, yearly and biennial results with the presentation of objective methods of control - urethrograms and uroflowmetry. Conclusions are given on the presented material, it was suggested to use this technique in certain groups of patients, to re-evaluate after accumulating a significant experience of such interventions.